Patency Capsule Aspiration - Takeda, Keita (Intern Med, 2020)
A 77-year-old man with anemia who had undergone 2 abdominal surgeries for colon and gastric cancer experienced dyspnea after swallowing a patency capsule before endoscopy for investigating the cause of anemia. Chest radiography and computed tomography revealed that the patency capsule was located within the bronchus intermedius. It was successfully removed by flexible bronchoscopy. The balloon was placed over the capsule and inflated. Subsequently, the catheter was pulled, while thus dragging the capsule with it and preventing its destruction. In cases of patency capsule aspiration, the capsule must be removed without deformity, before it causes inflammation by releasing barium into the airway.